2020
DOI: 10.17835/2076-6297.2020.12.3.060-082
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Financialization on Investment by Non-Financial Private Sector in Spain: an Empirical Analysis

Abstract: предполагалось, что небольшие фирмы будут увеличивать инвестиции при росте их финансовых доходов. Проведенное исследование может способствовать объяснению ослабления инвестиционной активности в Испании в последние десятилетия.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Our results are consistent with those of other authors obtained in other countries. So, for example, our results are comparable (but not completely so) to the results obtained by Tori and Onaran (2018) for the UK, Kuzmina and Rozmainsky (2020) for Spain-2020, Stockhammer (2004 for European countries , and Orhangazi (2008) for the USA. So, for example, we, like most authors, found that financial expenses have the strongest negative impact on investment in all companies and at all time periods.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our results are consistent with those of other authors obtained in other countries. So, for example, our results are comparable (but not completely so) to the results obtained by Tori and Onaran (2018) for the UK, Kuzmina and Rozmainsky (2020) for Spain-2020, Stockhammer (2004 for European countries , and Orhangazi (2008) for the USA. So, for example, we, like most authors, found that financial expenses have the strongest negative impact on investment in all companies and at all time periods.…”
Section: Discussionsupporting
confidence: 84%
“…Financial incomes had a positive effect on investment only for small British companies (Tori andOnaran, 2018, p. 1410). Furthermore, Kuzmina and Rozmainsky (2020) applied the same methodology to Spanish firms and came to the conclusion that, even for small companies, financial incomes had a negative effect on investment.…”
Section: The Post-keynesian Model Of Investment As the Starting Pointmentioning
confidence: 99%
“…Financialization can also be viewed from a behavioral perspective, as it can change some norms of economic behavior of economic entities, norms that affect the assessment of the future time. Some authors find financialization to be encouraging people to focus on high short-term economic outcomes (Kuzmina and Rozmainsky, 2020;Tretyakov and Rozmainsky, 2021). At the same time, this is found to be especially applicable to managers of firms who seek to raise the market value of the financial assets of these firms as high as possible in exchange for some "bonuses" from shareholders.…”
Section: Theoretical Aspects 21 Financialization and Its Aftermathmentioning
confidence: 99%
“…Studies of the implications of financialization mainly concern its impact on corporations' investment behavior, and many have already been carried out in some countries of the developed world, such as the US (Orhangazi, 2008;Lin and Tomaskovic-Devey, 2013), peripheral countries (Cibils and Allami, 2013;Rodrigues et al, 2016), some European countries (Stockhammer, 2004;Álvarez, 2012;Barradas et al, 2018;Alvarez, 2015;Tori and Onaran, 2018;Kuzmina and Rozmainsky, 2020) and Russia (Tretyakov and Rozmainsky, 2021). For Italy, such an analysis has been carried out as well due to the actuality of the issue for this country.…”
Section: Introductionmentioning
confidence: 99%